A new paradigm of islet adaptations in human pregnancy: insights from immunohistochemistry and proteomics - Faheem Seedat; Katie Holden; Simon Davis; Roman Fischer; James Bancroft; Edward Drydale; Neva Kandzija; John A. Todd; Manu Vatish; M. Irina Stefana (Nature Communications)
Abstract Physiological changes during pregnancy support foetal growth, including adaptations in pancreatic islets to maintain glucose homeostasis. We investigate these adaptations using rare, high-quality pancreatic tissue from pregnant human donors and matched controls. We profile islets from pregnant donors using proteomics and assess α- and β-cell characteristics, as well as prolactin receptor and serotonin 2B receptor expression. Proteomic profiling of microdissected human islets identifies 7546 proteins but shows minimal differences in protein expression. In pregnancy, we show that islet area increases 1.9-fold, α- and β-cell areas increase 4.3- and 1.9-fold, driven by an increase in cell number rather than hypertrophy. Prolactin receptor expression is higher in α but not β cells, and serotonin 2B receptor is undetectable in β cells. Glucagon-like peptide-1 abundance increases 2.9-fold in α cells. These findings indicate that the molecular mechanisms driving pregnancy-induced islet adaptations in humans differ from those in mice, highlighting the need for human-based studies.